In order to find the centroid of a polyhedral element (for finite volume method) bounded by a set of vertices, we follow the following procedure (from my textbook):

enter image description here

1 - Calculate the geometric centre $(x_g, y_g, z_g)$ of the polyhedron by summing all the vertices(points) and dividing by their total number, where:

$$ x_g = \frac{1}{n}\sum_n x_i$$

2 - Divide the polyhedron into a set of sub-pyramids, with the geometric centre as the apex with each surface polygon as the base.

3 - Calculate the centroid of each sub-pyramid, measured from the centroid of the base, is situated at 1/4 of the line joining the centroid of the base to the apex of the pyramid.

4 - And finally, the volume-weighted average can be calculated.

The part that I don't understand is the part of calculating the centroid of the sub-pyramids, my textbook uses the following equation:

$$ (x_{CE})_{pyramid} = 0.75(x_{CE})_f + 0.25(x_G)_{pyramid} $$

where $x_{CE}$ is the centroid of the pyramid we want to calculate, $(x_{CE})_f$ if the centroid of the polygonal base and $x_g$ is the geometric centre of the pyramid.

So, how does point number 3 relates to the previous formula?

  • 1
    $\begingroup$ There seem to be some extra parentheses and a "pyramid" subscript in your last formula that should not be in that formula. $\endgroup$ – David K Sep 13 '16 at 15:05

$$ (x_{CE})_{pyramid}=(x_{CE})_f+{1\over4}(x_{G}-(x_{CE})_f)={3\over4}(x_{CE})_f+{1\over4}x_{G}. $$


Let's call the position vector of the apex of the pyramid $\vec{G}$. Let's call the position vector of the base's center of mass $\vec{K}$. In addition, let's call the height of the pyramid $h$ and the area of the base $A$. The volume of the pyramid is then $V=\frac{1}{3}Ah$. Consider the the position vector $\vec{P}=\vec{G} + \frac{\lambda}{h} (\vec{K}-\vec{G})$, for $0\leq \lambda \leq h$. The area of the horizontal cross section of the pyramid at $\vec{P}$ has area $A_{\vec{P}}=\left(\frac{\lambda}{h}\right)^2A$. To calculate the center of mass of the pyramid, we can calculate the following integral:

\begin{align} \frac{1}{V}\int_0^hA_{\vec{P}} \vec{P}d\lambda &= \frac{3}{Ah}\int_0^h\left(\frac{\lambda}{h}\right)^2 A\left(\vec{G} + \frac{\lambda}{h} (\vec{K}-\vec{G})\right)d\lambda\\ &=\frac{3}{Ah}\int_0^h\left[\left(\frac{\lambda}{h}\right)^2 A\vec{G} + \left(\frac{\lambda}{h}\right)^3 A(\vec{K}-\vec{G})\right]d\lambda\\ &=\frac{3}{Ah}\left[\frac{h^3}{3h^2} A\vec{G} + \frac{h^4}{4h^3} A(\vec{K}-\vec{G})\right]\\ &=\vec{G}+\frac{3}{4} (\vec{K}-\vec{G})\\ &=\frac{1}{4}\vec{G}+\frac{3}{4}\vec{K} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.